Response of Nutrient Omission and Irrigation Scheduling on Growth and Productivity of Maize - Acharya, N.R.; Sah, S.K.; Gautam, A.K.; Regmi, A.P. (International Journal of Applied Sciences and Biotechnology, 2020)
An experiment was conducted for response of nutrient omission to irrigation scheduling in hybrid maize during winter season of 2015 at farmer’s field Khajura, Banke where intense summer and severe winter occurs. Soil is sandy loam and climatically humid sub-tropical with average annual rainfall of 1000-1500 mm. The experiment was replicated 3 times with split plot design having plot size of 3 x 3.6 m2. There were three irrigation level as main plot; (30 -35 DAS, tasseling stage), (30-35 DAS, tasseling, grain filling stage), (tasseling stage) and six level of fertilizer dose as sub-plot; farmer fertilization practice (27.6:27.6:18 N-P-K kg ha-1), recommended dose of fertilizer (160:60:40 N-P-K kgha-1), 50 percent above recommended dose (240: 90: 60 N-P-K kg ha-1), N0PK (60:40 P-K kg ha-1), NP0K (160:40 N-K kg ha-1), NPK0 (160:60 N-P kg ha-1). 3 level of irrigation increased the grain yield (4333 kg ha-1) by 33.7% than 2 level of irrigation (3240.6 kg ha-1) and 78.4% than single irrigation (2428.8 kg ha-1). Similarly, 182.4% grain yield could be increased with RDF (4994.9 kg ha-1) than N0PK (1768.6 kg ha-1). Grain nutrient uptake was recorded 80.4% N (56.3 kg ha-1), 79% P (18.8 kg ha-1), 88.8% K (15.1 kg ha-1) higher with three levels of irrigation than single irrigation N (31.2 kg ha-1), P (10.5 kg ha-1), K (8 kg ha-1) and 184% N (64.6 kg ha-1), 183.7% P (21 kg ha-1) and 188% K (17 kg ha-1) was recorded higher with RDF than (N0PK) N (22.7 kg ha-1), P (7.4 kg ha-1), K (5.9 kg ha-1). Int. J. Appl. Sci. Biotechnol. Vol 8(3): 343-354